2018
DOI: 10.1142/s0129055x18500046
|View full text |Cite
|
Sign up to set email alerts
|

On the algebraic quantization of a massive scalar field in anti-de Sitter spacetime

Abstract: Abstract. We discuss the algebraic quantization of a real, massive scalar field in the Poincaré patch of the (d + 1)-dimensional anti-de Sitter spacetime, with arbitrary boundary conditions. By using the functional formalism, we show that it is always possible to associate to such system an algebra of observables enjoying the standard properties of causality, time-slice axiom and F-locality. In addition, we characterize the wavefront set of the ground state associated to the system under investigation. As a co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…We shall illustrate this fact by using the free Klein-Gordon theory as an example. Thus, our results also provide a bridge between the ideas of [30] and the concrete constructions in [8,[10][11][12].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…We shall illustrate this fact by using the free Klein-Gordon theory as an example. Thus, our results also provide a bridge between the ideas of [30] and the concrete constructions in [8,[10][11][12].…”
Section: Introductionsupporting
confidence: 62%
“…For specific choices of boundary conditions, there exist successful constructions of algebraic quantum field theories on spacetimes with timelike boundary, see e.g., [8,[10][11][12]. The main message of these works is that the algebraic approach is versatile enough to account also for these models, although some key structures, such as for example the notion of Hadamard states [11,32], should be modified accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…These boundary conditions appear frequently in the physics literature; see e.g. [DF2,DFM]. Further motivation comes from the study of the Dirichlet-to-Neumann operator, which was recently shown to coincide with a power of the wave operator in the case of a static metric [EdMGV].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…To answer this question we follow the same procedure as in [8][9][10] which relies on Sturm-Liouville theory for ordinary differential equations. A reader interested in more details can consult [18] on which we base our analysis.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The techniques used in [8] are rather flexible; they have been studied from a rigorous viewpoint in [9] and applied also to the analysis of a Klein-Gordon field in BTZ spacetime in [10]. In this paper, first we also apply them to the study of a massive, real scalar field in the global chart of CAdS n , in order to investigate if the results obtained in the Poincaré patch do extend globally.…”
Section: Introductionmentioning
confidence: 99%